Closing the gap: a novel technique for humeral shaft nonunions using cup and cone reamers. (December 2016) - Nickel, Brian T.; Klement, Mitchell R.; Richard, Marc J.; Zura, Robert; Garrigues, Grant E.
Abstract: Introduction: Nonunion following closed treatment of humeral shaft fracture is estimated to be 5.5%. Many surgical techniques have been described to address humeral shaft nonunion including: open reduction, internal fixation (ORIF) with compression plating and bone graft, dual plating, cortical strut allograft and autograft, and adding biologic augmentation (BMP). The current standard of care includes ORIF with compression plating and bone grafting, but even this technique has an approximated 10% failure rate. We describe a novel surgical technique using cup and cone reamers, which were originally designed for metatarsophalangeal or metacarpalphalangeal arthrodesis. Cup and cone reamers are the appropriate size for mid-shaft, transverse humeral nonunions to ensure ideal apposition of healthy, bleeding bone. Methods and patients: We retrospectively reviewed 3 patients with nonunion of the midshaft humerus which were treated with the cup and cone technique and a large fragment LCDC plate. An anterolateral approach was used in 2 cases and a posterior in the other. After exposure of fracture ends, 24-mm hemispherical convex and concave reamers were then used to ream the proximal and distal ends in order to create a "cup and cone" articulation of the fracture ends. All patients were followed for a minimum of 6 months with a mean follow-up of 12 months. Results: All patients treated with this technique achieved union, reported zero pain and full functional outcome. Specifically, patients had a mean age of 36.3 and the mean interval between injury and time to surgery was 11.5 months. Two of the patients presented with nonunions after attempted closed treatment and the other patient had 3 prior surgeries for infected nonunion. Union was achieved at a mean of 12 weeks. Conclusion: To our knowledge, the use of cup and cone reamers for nonunion of the humerus has never been described. We describe a simple and effective technique for humeral shaft nonunions which has been successful in both septic and hypertrophic nonunions, as well as from multiple approaches-both anterolateral and posterior.